Descrição da larva de Cosmariomyia argyrosticta Kertész e do pupário de Dactylodeictes lopesi Lindner (Diptera, Stratiomyidae) - Xerez,Roberto de (2002)
The larva of Cosmariomyia argyrosticta Kertész, 1914 and the puparium of Dactylodeictes lopesi Lindner, 1964 are described for the first time, based on four larvae and 10 puparia and one puparium respectively. Larvae were collected under the bark of fallen trees in an area near of tropical rain forest at Iguaba Grande (22º50'21"S, 42º13'44"W, 18 m) and Buzios (22º44'49"S, 41º52'54"W, 3 m), State of Rio de Janeiro, Brazil. Some biological notes are also presented. The larvae of Cosmariomyia argyrosticta and Dactylodeictes lopesi are compared with Chalcidomorphina aurata Enderlein, 1914 and Vittiger schnusei Kertész, 1909.